Getting it published [ a guide for scholars and anyone else serious about serious books - Germano, William P. , 1950- (Chicago guides to writing, editing, and publishing, 2008)
"Germano, a veteran editor with experience in both the university press and commercial worlds, knows his audience. This second edition will teach readers how to think about, describe, and pitch their manuscripts before they submit them. They'll discover the finer points of publishing etiquette, including how to approach a busy editor and how to work with other publishing professionals on matters of design, marketing, and publicity. In a new afterword, they'll also find helpful advice on what they can - and must - do to promote their work." "A true insider's guide to academic publishing, the second edition of Getting It Published will help authors understand what to expect from the publishing process, from manuscript to finished book and beyond."--BOOK JACKET